Identity, ecology and ecophysiology of planktic green algae dominating in ice-covered lakes on James Ross Island (northeastern Antarctic Peninsula) - Nedbalová, Linda; Mihál, Martin; Kvíderová, Jana; Procházková, Lenka; Řezanka, Tomáš; Elster, Josef (Extremophiles, 2017)
The aim of this study was to assess the phylogenetic relationships, ecology and ecophysiological characteristics of the dominant planktic algae in ice-covered lakes on James Ross Island (northeastern Antarctic Peninsula). Phylogenetic analyses of 18S rDNA together with analysis of ITS2 rDNA secondary structure and cell morphology revealed that the two strains belong to one species of the genus Monoraphidium (Chlorophyta, Sphaeropleales, Selenastraceae) that should be described as new in future. Immotile green algae are thus apparently capable to become the dominant primary producer in the extreme environment of Antarctic lakes with extensive ice-cover. The strains grew in a wide temperature range, but the growth was inhibited at temperatures above 20 °C, indicating their adaptation to low temperature. Preferences for low irradiances reflected the light conditions in their original habitat. Together with relatively high growth rates (0.4-0.5 day-1) and unprecedently high content of polyunsaturated fatty acids (PUFA, more than 70% of total fatty acids), it makes these isolates interesting candidates for biotechnological applications.
Keywords: Fatty acids; Phytoplankton; biodiverzita; RNA, Ribosomal, 18S; Ecology; Ice-covered lakes; Ice Cover; Antarctica; Monoraphidium; jezera; Chlorophyta; fyziologická adaptace; Fatty Acids, Unsaturated; Light; Phylogeny; Temperature; Antarktida; nenasycené mastné kyseliny; Antarctic Regions; RNA ribozomální 18S; Biodiversity; Adaptation, Physiological; ledový příkrov; Lakes; fytoplankton